Desain Signage dan Street Furniture di Kawasan Wisata Desa Wisata Karyamukti - Muhammad Jasoma; Agus Suparman (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2023)
Gunung Padang Cultural Heritage Site is a National Cultural Reserve in the form of a stepped punden building that is the largest and oldest in Indonesia. The location is in Karyamukti Village, Campaka District, Cianjur Regency, West Java. The tourist area in Karyamukti Village has a variety of unique tourist areas that can be enjoyed by tourists, including a welcome/reception area that serves to provide information to tourists. Activities carried out by tourists in Karyamukti Tourism Village, of course, must get the attention of tour managers. In the receiving area and some areas that will be used as locations for receiving tourists must be equipped with facilities in the form of signage and street furniture. The existence of signage and street furniture in tourist areas will certainly be able to provide information and meet the needs of tourists who come to tourist locations in Karyamukti Tourism Village. And the character of the signage design and street furniture must also be able to represent the character of the region by raising local wisdom. This signage character is a visual form used to convey a message to the person who sees it. Signage has unique and different characters, depending on the destination and location to be marked. Signage characters can be colors, shapes, sizes, and font types used. Signage can also use symbols and icons to convey messages. Keywords: culture, tourist village, local wisdom, signage, street furniture